Senna hatschbachii (Leguminosae, Caesalpinioideae): a newly discovered endangered species from the Brazilian Atlantic Forest - Souto, Flávio Sousa; Queiroz, Rubens Teixeira De; Agra, Maria De Fátima (Phytotaxa, 2025)
Senna hatschbachii, a new species of Senna sect. Peiranisia ser. Interglandulosae, is endemic to Brazil and occurs in the Atlantic Forest of northern Paraná State. The species is described and illustrated here employing traditional taxonomic criteria based on collections from Brazilian herbaria. Morphologically, Senna hatschbachii is closely related to Senna multijuga var. lindleyana, although it differs by having linear stipules ≤ 0.1 mm wide, a subulate extrafloral nectary between the first pair of leaflets, and leaves with 6–13 pairs of leaflets (vs. setiform stipules with 0.2–0.4 mm wide, an ovoid to narrow-ovoid extrafloral nectary located between the first pair of leaflets and occasionally between subsequent pairs, and leaves with 15–46 pairs of leaflets in S. multijuga var. lindleyana). Its morphological and anatomical traits, identification key, geographic distribution, and habitat are discussed, along with a preliminary conservation assessment following IUCN Red List guidelines. In addition, we also provide a key for identifying tree taxa of Senna ser. Interglandulosae in Brazil.